Functional connectomics spanning multiple areas of mouse visual cortex - J. Alexander Bae; Mahaly Baptiste; Maya R. Baptiste; Caitlyn A. Bishop; Agnes L. Bodor; Derrick Brittain; Victoria Brooks; JoAnn Buchanan; Daniel J. Bumbarger; Manuel A. Castro; Brendan Celii; Erick Cobos; et al. (Nature, 2025)
Abstract Understanding the brain requires understanding neurons’ functional responses to the circuit architecture shaping them. Here we introduce the MICrONS functional connectomics dataset with dense calcium imaging of around 75,000 neurons in primary visual cortex (VISp) and higher visual areas (VISrl, VISal and VISlm) in an awake mouse that is viewing natural and synthetic stimuli. These data are co-registered with an electron microscopy reconstruction containing more than 200,000 cells and 0.5 billion synapses. Proofreading of a subset of neurons yielded reconstructions that include complete dendritic trees as well the local and inter-areal axonal projections that map up to thousands of cell-to-cell connections per neuron. Released as an open-access resource, this dataset includes the tools for data retrieval and analysis 1,2 . Accompanying studies describe its use for comprehensive characterization of cell types 3–6 , a synaptic level connectivity diagram of a cortical column 4 , and uncovering cell-type-specific inhibitory connectivity that can be linked to gene expression data 4,7 . Functionally, we identify new computational principles of how information is integrated across visual space 8 , characterize novel types of neuronal invariances 9 and bring structure and function together to uncover a general principle for connectivity between excitatory neurons within and across areas 10,11 .